The Impact of Time Interval Between First Extubation and Reintubation on Bronchopulmonary Dysplasia or Death in Very Low Birth Weight Infants - Li, Jing; Zhang, Jing; Hao, Qingfei; Shen, Ziyun; Du, Yanna; Chen, Haoming; Cheng, Xiuyong (Frontiers in Pediatrics, 2022)
Objective: To explore the relation between time from first extubation to reintubation and moderate-to-severe bronchopulmonary dysplasia (BPD) or death in very low birth weight infants. Study design: Infants with birth weight＜1500 g, requiring mechanical ventilation, and undergoing their initial extubation were retrospectively included from January 2014 to December 2021. They were divided into moderate-to-severe BPD/death group and control group according to the incidence of moderate-to-severe BPD or death. Time to reintubation was defined as the time interval between first extubation and reintubation. Stepwise multivariate logistic regression analyses were performed to evaluate associations between time to reintubation and moderate-to-severe BPD/death using different observation windows after initial extubation (24-hour intervals). Results: A total of 244 infants were recruited, including 57 cases in the moderate-severe BPD/ death group and 187 cases in the control group, and 93 (38.1%) cases were reintubated at least once after their first extubation. Univariate analysis showed that reintubation rates within different observation windows in the moderate-to-severe BPD/death group were higher than those in the control group, with statistical significance (P<0.05). Multivariate regression analysis showed that reintubation within observation windows 48 hours or 72 hours postextubation was an independent risk factor of moderate-to-severe BPD/death and death, but not moderate-to-severe BPD. When the time window was 48 hours, the probability of moderate-to-severe BPD/death (odds ratio [OR]: 3.778, 95% confidence interval [CI]: 1.293-11.039) or death (OR: 4.734, 95% CI: 1.158-19.354) was highest. While after extending the observation window to include reintubations after 72 hours from initial extubation, reintubation was not associated with increased risk of moderate-to-severe BPD and/or death. Conclusions: Not all reintubations conferred increased risks of BPD/death. Only reintubation within 72 hours from initial extubation was independently associated with increased likelihood of moderate-to-severe BPD/death and death in very low birth weight infants, and the greatest risk was attributable to reintubation within the first 48 hours postextubation.